On Describing Similarity and Measuring Equivalence in English-Spanish Translation - Izquierdo, Marlén (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
This article reports on a descriptive translation study that attempts to examine the notion of equivalence in translation in an empirical manner. In order to do that, the analysis focuses on the similarities and differences, considered as the components of any relation of equivalence, between the source texts and the target texts. In this particular case, the source texts are English Gerund-Participle (G-P) Adjuncts, and their target texts, the Spanish translational options found in so-called “ACTRES parallel corpus.” The study is interdisciplinary as it draws from contrastive functional analysis and descriptive translation studies, from a corpus-based approach. The study reveals different types of similarities between the English G-P Adjuncts and its Spanish equivalents, which are described in functional terms, taking into consideration functionality, meaning-form interface and frequency of usage. The descriptive parameters followed have prompted a grading system for measuring equivalence between the objects of study.